Genomic Characterization of WRKY Transcription Factors Related to Andrographolide Biosynthesis in Andrographis paniculata - Zhang, Rongrong; Chen, Zhenzhen; Zhang, Libing; Yao, Wei; Xu, Zhichao; Liao, Baosheng; Mi, Yaolei; Gao, Han; Jiang, Chunhong; Duan, Lixin; Ji, Aijia (Frontiers in Genetics, 2021)
Andrographolide, which is enriched in the leaves of Andrographis paniculata, has been known as “natural antibiotic” due to its pharmacological activities such as anti-inflammatory, antimicrobial and antioxidant effects. Several key enzymes in andrographolide biosynthetic pathway have been studied since the genome sequences were released, but its regulatory mechanism remains unknown. WRKY transcription factors proteins have been reported to regulate plant secondary metabolism, development as well as biotic and abiotic stresses. Here, WRKY transcription factors related to andrographolide biosynthesis were systematically identified, including sequences alignment, phylogenetic analysis, chromosomal distribution, gene structure, conserved motifs, synteny, alternative splicing event and GO annotation. A total of 58 WRKYs were identified in Chuanxinlian genome and phylogenetically classified into 3 groups. Moreover, nine WRKY genes underwent alternative splicing events. Furthermore, the combination of binding site prediction, gene-specific expression patterns, and phylogenetic analysis suggested that 7 WRKYs (ApWRKY01, ApWRKY08, ApWRKY12, ApWRKY14, ApWRKY19, ApWRKY20 and ApWRKY50) might regulate andrographolide biosynthesis. This study laid a foundation for understanding the regulatory mechanism of andrographolide biosynthesis and the improvement and breeding of Andrographis paniculata varieties.